Revocation Of Re-Elected Rights For Corruptor In Public Offices Without Time Limitation The Progressive Law Perspective - Fira Mubayyinah (IAIN Padangsidimpuan, 2019)
The problem of corruption has always been a public discussion, not only because of its consequences. But also because the perpetrators of corruption that they caught were from political parties. And it tends to be after they go through the criminal period, re-enter the area of policy holders or authority through political channels again. Additional criminal imposition of revocation of political rights for the corutor is stated in the Decision of the Supreme Court Number: 537k / Pid.Sus / 2014, and Number 1195K / Pid.Sus / 2014. The application is not limited to the period as stipulated in article 38 of the Criminal Code. Revocation of political rights on the one hand is considered contrary to human rights, but revocation of political rights becomes an important punishment imposed, considering that the perpetrators of corruption do not come from political parties. The application of criminal acts is a means of reason to prevent criminal acts. Revocation of political rights which is still debated can have an impact on its implementation. Therefore, in its implementation, of course requires a Law Enforcement Officer who has a step of thinking and progressive steps. Penal punishment is the authority of the Judge. Judges in imposing crimes should rely on the principle of substantive justice and are intended to provide protection to society (social deffence)